Assessment of Reductions in Emission-driven Air Pollution during the Beijing Olympic Games, Shanghai World Expo, Guangzhou Asian Games and Wuhan COVID-19 Lockdown - Ying Li; Haoxiang Xu (Aerosol and Air Quality Research)
Abstract Quantifying and comparing the effectiveness of different emission control strategies can provide insights for policy design and air quality management. In our previous work, we developed a wind-pollution decomposition (WPD) method that provides a robust tool to quantify meteorology-driven and emission-driven impacts on changes in air quality. In this study, we applied this method to quantify emission-driven impacts on the observed air quality changes during the three largest international socioeconomic mega-events in China, namely, Shanghai World Expo in 2010, Beijing Olympic Games in 2008, and Guangzhou Asian Games in 2010. We also applied the method to the air quality variation during the lockdown period in Wuhan due to COVID-19 and compared the emission-driven impacts on air quality among these events. The results quantitatively show that the emission-driven factor generally played a much stronger role (> 86%); the meteorology-driven factor promoted pollution mitigation during Wuhan, Beijing and Guangzhou events but worsened the air quality during Shanghai event. The emission-driven pollution reduction was largest in the Wuhan COVID-19 lockdown (64% NO2, 54% PM2.5 reductions), followed by Beijing Olympics (42% PM2.5, 31% NO2 reductions), The Wuhan COVID-19 impact on air quality improvement is not as effective as expected especially for O3, which implies the difficulty of air quality attainment under normal, non-lockdown days. Comparison of these events show that shutdown or emission control measures applied to industries and power plants were generally benefit for PM2.5, SO2 and NO2 reduction, while those applied to on-road traffic control are less-effective for reducing NO2 and not works for the mean O3 reduction. The results imply that advanced control measures for vehicle exhaust and control strategies considering the interaction between O3 and NOx/VOC/PM are necessary. In addition, the ongoing supervision of control strategies implementation is one of the key issues for future air quality management in China.